PREPARATION OF FLIGHT FAN DOCTOR BLADE DETAILS ON ROBOTIC GRINDING (RDB) MACHINES: A COMPREHENSIVE STUDY ON PRECISION, SURFACE INTEGRITY, AND PROCESS OPTIMIZATION - K. H. Abdullayev; U. B. Ergashev (Modern American Journals, 2026)
The manufacturing of flight fan doctor blades represents a critical aerospace component production challenge, demanding exceptional precision, surface quality, and material integrity. This study comprehensively investigates the preparation of these components using Robotic Grinding (RDB) machines, addressing the intersection of advanced automation with high-precision material processing requirements.
Keywords: Robotic grinding, flight fan blades, aerospace manufacturing, force compliance control, surface integrity, dislocation density, adaptive machining, precision grinding, material removal rate, process optimization